2003
DOI: 10.1074/jbc.m211570200
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Recruitment of ERK1/2 and p38 MAPK Signalling Pathway Is Required for Activation of Cytoplasmic Phospholipase A2via ATP in Articular Chondrocytes

Abstract: Extracellular ATP is a pro-inflammatory mediator involved in the release of prostaglandin from articular chondrocytes, but little is known about its effects on intracellular signaling. ATP triggered the rapid release of prostaglandin E 2 (PGE 2 ) by acting on P2Y 2 receptors in rabbit articular chondrocytes. We have explored the signaling events involved in this synthesis. ATP significantly increased arachidonic acid production, which involved the activation of the 85-kDa cytosolic phospholipase A 2 (cPLA 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…receptor stimulation increased IL-1-mediated PGE2 release from articular chondrocytes (Koolpe et al, 1999) and induced a rapid rise in PGE2 synthesis via the ERK1/2 and p38 MAPK signalling pathways (Berenbaum et al, 2003). In contrast, early work suggested that ATP caused articular cartilage mineralisation by promoting matrix vesicle-mediated calcium deposition (Ryan et al, 1992;Hsu, 1992).…”
Section: Functional Effects Of P2 Receptor Signalling In Chondrocytesmentioning
confidence: 99%
“…receptor stimulation increased IL-1-mediated PGE2 release from articular chondrocytes (Koolpe et al, 1999) and induced a rapid rise in PGE2 synthesis via the ERK1/2 and p38 MAPK signalling pathways (Berenbaum et al, 2003). In contrast, early work suggested that ATP caused articular cartilage mineralisation by promoting matrix vesicle-mediated calcium deposition (Ryan et al, 1992;Hsu, 1992).…”
Section: Functional Effects Of P2 Receptor Signalling In Chondrocytesmentioning
confidence: 99%
“…Cell lysates were separated by 10% or 15% SDS-polyacrylamide gel electrophoresis and transferred to PVDF membranes (31). The blots were soaked in Tween 20 in Tris buffered saline (TBST; 20 mM Tris HCl, pH 7.5, 100 mM NaCl, 0.1% Tween 20, and 5% BSA) for 2 hours at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…PGE 2 assay. The PGE 2 concentrations in aliquots of supernatants from cultures of stimulated chondrocytes were measured using a PGE 2 enzyme immunoassay kit (Cayman Chemical, Ann Arbor, MI), as previously described (31). PGE 2 concentrations were assayed in duplicate and were read against a standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of p38 induces the synthesis of key inflammatory mediators such as TNF-α, IL-1, IL-6, IL-8, and cyclooxygenase-2, either via direct activation of gene transcription or via mRNA stabilization (Winzen et al, 1999;Paccani et al, 2002). In addition, p38 mediates the synthesis of other compounds involved in inflammation, including chemokines and adhesion molecules, the metalloproteinases responsible for cartilage breakdown, and prostaglandins (Berenbaum et al, 2003). In the context of bone erosion, p38 mediates TNF-α-induced IL-1 upregulation in stromal cells and the subsequent IL-1-induced RANKL production.…”
Section: Discussionmentioning
confidence: 99%